The use of microbead-based spoligotyping for Mycobacterium tuberculosis complex to evaluate the quality of the conventional method: Providing guidelines for Quality Assurance when working on membranes - Abadia, Edgar (2011)
Fil: Abadia, Edgar. CNRS Université Paris-Sud 11 Universud. Institute of Genetics and Microbiology UMR8621; Francia.